Trust Mediates Religious Commitment and Halal Cosmetics Consumption: A SEM Analysis - Razak, Syaparuddin (EQUILIBRIUM, 2023)
The main purpose of this study is to contribute to the literature by focusing on the relationship between religious commitment and halal cosmetics consumption and identifying the mediating effect of middle-class Muslim females’ trust on halal cosmetics consumption. We used structural modeling (Lisrel) in investigating these relationship and applied non-probability convenience sampling to administer questionnaires among 450 middle-class Muslim female respondents currently living in South Sulawesi, Indonesia. The results showed that the direct effect of religious commitment, ability, benevolence, and integrity on trust showed T-Values of 1.71, 2.61, -1.92. These indicate that only ability has a significant and positive effect on trust, but the direct effect of trust, religious commitment, ability, benevolence, and integrity on halal cosmetics consumption showed T-Values of 4.11, 1.71, 2.60, -2.12. These indicate that only trust and ability have significant and positive effects on halal cosmetics consumption. Meanwhile the mediating role of trust showed T-Values of 1.41, 2.79, -2.12, and 1.86. These indicate that trust was significantly and positively found in mediating the relationship between ability and halal cosmetics consumption, but in the relationship between benevolence and halal cosmetics consumption, it was also significantly found but negatively.